Is the Blood Pressure Paradox Observed in All Heart Failure Patients?. (25th November 2013) - Cunha, F. M.; Lourenço, P.; Couto, M.; Tavares, P.; Silva, S.; Guimarães, J. T.; Bettencourt, P.
Abstract : Background. Heart failure (HF) patients with higher systolic blood pressure (SBP) survive longer. Diabetes mellitus (DM) is a frequent comorbidity in HF. We evaluated the prognostic significance of low SBP according to DM in acute HF. Methods. We prospectively recruited 589 patients admitted with acute HF. DM was defined according to the 2011 American Diabetes Association recommendations. Patients were followed for 6 months and HF-death was the endpoint. A multivariate Cox-regression model was used to assess the prognostic impact of SBP. A stratified analysis according to DM was performed. Results. Median patients' age was 79 years and DM was present in 50.8%. Ischemic aetiology HF and hypertension history were more common in diabetics. Diabetic patients had worse renal function and lower total cholesterol and were more often discharged with antiplatelet therapy and statin. During followup, 89 patients died due to HF. The multivariate-adjusted HR for the 6-month HF death in non-diabetic patients with an admission SBP < 115 mmHg (1st quartile) was 2.94 (95% CI: 1.49–5.79), while lower admission SBP was not associated with HF mortality in diabetics. Conclusions. The blood pressure paradox in HF is only observed in non-diabetic HF patients. Diabetic patients seem to be a particular subgroup of HF patients.